2009
DOI: 10.1111/j.1471-0307.2009.00526.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Lallemantia royleana (Balangu) seed, palmate‐tuber salep and carboxymethylcellulose gums on the physicochemical and sensory properties of typical soft ice cream

Abstract: This study was aimed primarily at determining the suitability of two Iranian sources of hydrocolloid, Balangu seed and palmate‐tuber salep (PTS), for the production of ice cream mix. For this purpose, the effect of these gums and carboxymethylcellulose (CMC) on some physicochemical and sensory characteristics of a typical soft ice cream was investigated. In comparison with carboxymethylcellulose, Balangu seed did not make a significant difference (P > 0.05) to most characteristics and could be used as a suitab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 17 publications
5
24
1
1
Order By: Relevance
“…Uzomah and Ahiligwo (1999) reported that the quality characteristics of ice cream produced from Ogbono seed gum appeared to be close to those of the control sample (without stabilisers). In contrast to our study, Bahramparvar et al (2009) mentioned that no difference was observed between Balangu seed gum and carboxymethylcellulose in the melting resistance of the ice creams.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Uzomah and Ahiligwo (1999) reported that the quality characteristics of ice cream produced from Ogbono seed gum appeared to be close to those of the control sample (without stabilisers). In contrast to our study, Bahramparvar et al (2009) mentioned that no difference was observed between Balangu seed gum and carboxymethylcellulose in the melting resistance of the ice creams.…”
Section: Resultscontrasting
confidence: 99%
“…In contrast to our study, Bahramparvar et al . () mentioned that no difference was observed between Balangu seed gum and carboxymethylcellulose in the melting resistance of the ice creams.…”
Section: Resultsmentioning
confidence: 98%
“…There was a trend to lower pH and higher acidity in mixtures with increasing QSSG and CSG but no significant effect was observed in pH and acidity of samples containing the two gums (p [ 0.05). This finding is in agreement with the results of Bahramparvar et al (2009). They found that addition of Lallemantia royleana (Balangu) seed, palmate-tuber salep and carboxymethylcellulose gums in ice cream lead to non significant changes in the ice cream pH and acidity.…”
Section: Ph and Aciditysupporting
confidence: 83%
“…It can be seen that the highest viscosity values were obtained at the experimental zone where gums concentrations were higher (0.12 \ QSSG \ 0.2% and 0.05 \ CSG \ 0.2%). Many studies have investigated the viscosity and rheological characteristics of ice cream and ice cream mixtures (Soukoulis et al 2008;Wittinger and Smith 1986;Bahramparvar et al 2013;Mahdian and Karazhian 2013;Rezaei et al 2011;Varela et al 2014;Martinou-Voulasiki and Zerfiridis 1990;Kaya and Tekin 2001;Bahramparvar et al 2009). They reported that stabilizers are macromolecules (mostly polysaccharides), that are able to interact with water and also interact with proteins and lipids in the mixture and so increase the mixture viscosity (Bahramparvar and Mazaheri-Tehrani 2011).…”
Section: Viscositymentioning
confidence: 99%
“…Its common Persian name is Balangu-Shirazi [1]. Some potentials of the mucilage isolated from its seeds as a new source of hydrocolloid have been recently investigated [2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%